Correlation between Inferior Vena Cava Diameter Assessed on Ultrasonography and Central Venous Pressure among Critically ILL Patients Admitted In Intensive Care Unit - Shabih Zehra; Atif Latif; Asiya Kazi; Syed Ijaz Hussain Zaidi (Journal of Bahria University Medical and Dental College)
Objective: To assess the correlation between inferior vena cava(IVC) diameter and central venous pressure (CVP) in critical patients admitted in ICU. Study Design and Setting: The cross-sectional pilot study was conducted at Radiology Department of PNS SHIFA Hospital. Methodology: 18-80 years patients were included and patients with severe orthopnea, unable to lie in supine position, morbid obese, pneumothorax, mass in mediastinum, tricuspid regurgitation and intra-cerebral bleeds were excluded. Results: The mean age of 50 patients was 41.44±16.73 years. Mean measurement of CVP was considered as 10.41±4.18 mm. Mean diameter of IVC was 12.65±2.22 mm. The study results showed weak negative correlation between the CVP and IVC (r= - 0.110, p=0.04). It was also predicted that patients with age =50 years showed weak negative correlation between the CVP and IVC (r=-0.290, p=0.034). Similarly, in patients with age >50 years there was strong negative correlation between CVP and IVC (r=-0.680, p=0.045). The study results also showed that in male patients there was weak negative correlation between the CVP and IVC i.e. (r=-0.045, p=0.048). However, in female patients there was moderate positive correlation (r=0.685, p=0.001). Conclusion: Weak negative correlation was found between inferior vena cava diameter on ultrasonography and central venous pressure measurement among critically ill patients